3D printing of essential oil/β-cyclodextrin/popping candy modified atmosphere packaging for strawberry preservation. (1st December 2022) - Li, Suqing; Jiang, Yalan; Wang, Min; Li, Runze; Dai, Jianwu; Yan, Jing; Qin, Wen; Liu, Yaowen
Abstract: In this study, lemongrass essential oil (LEO) was wrapped in β-cyclodextrin (β-CD) using a co-precipitation method to prepare an inclusion complex (LEO/β-CD). A biological multifunctional preservation card was prepared by 3D printing and mixing the inclusion complex with sodium alginate (SA). The moisture generated by strawberry respiration melted the popping candy (PPC) and stimulated the release of CO2, a synergistic antibacterial compound formed with LEO. Hence, antibacterial activity and air regulation were achieved, and the fruit remained fresh. The results indicated that LEO was successfully encapsulated in β-CD, and that LEO/β-CD had a strong bacteriostatic effect on Aspergillus niger and Botrytis cinerea, with a high resistance to oxidation. The PPC could release CO2 and extend the shelf life of strawberries by reducing their respiration and inhibiting mold. Graphical abstract: Unlabelled Image